2017
DOI: 10.3389/fpls.2017.02078
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed microRNAs and Target Genes Associated with Plastic Internode Elongation in Alternanthera philoxeroides in Contrasting Hydrological Habitats

Abstract: Phenotypic plasticity is crucial for plants to survive in changing environments. Discovering microRNAs, identifying their targets and further inferring microRNA functions in mediating plastic developmental responses to environmental changes have been a critical strategy for understanding the underlying molecular mechanisms of phenotypic plasticity. In this study, the dynamic expression patterns of microRNAs under contrasting hydrological habitats in the amphibious species Alternanthera philoxeroides were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 96 publications
0
8
0
Order By: Relevance
“…miRNAs have an active role in response to flooding in plants as revealed by genome-wide studies in response to hypoxia (Moldovan et al, 2010; Licausi et al, 2011b), waterlogging (Liu et al, 2012; Zhai et al, 2013), and submergence (Zhang et al, 2008; Jeong et al, 2013; Jin et al, 2017; Li et al, 2017; Franke et al, 2018). Despite the fact that reports of miRNA’s responsiveness to flooding stress are still scarce in comparison to reports on other abiotic stress, existing studies have revealed that miRNAs regulate four main lines of response to flooding stress including morphological adaptation, management of energy supply, control of flowering, and oxidative stress response (Figure 2).…”
Section: Rna Dynamics Under Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…miRNAs have an active role in response to flooding in plants as revealed by genome-wide studies in response to hypoxia (Moldovan et al, 2010; Licausi et al, 2011b), waterlogging (Liu et al, 2012; Zhai et al, 2013), and submergence (Zhang et al, 2008; Jeong et al, 2013; Jin et al, 2017; Li et al, 2017; Franke et al, 2018). Despite the fact that reports of miRNA’s responsiveness to flooding stress are still scarce in comparison to reports on other abiotic stress, existing studies have revealed that miRNAs regulate four main lines of response to flooding stress including morphological adaptation, management of energy supply, control of flowering, and oxidative stress response (Figure 2).…”
Section: Rna Dynamics Under Stressmentioning
confidence: 99%
“…Based on the previous knowledge that miR167 controls the expression of ARFs to regulate adventitious and lateral root development (Gutierrez et al, 2009), regulation of ARFs by miR167 in maize roots could have a balancing effect between suppressing primary root growth and promoting adventitious rooting in response to flooding in a time-scale manner. MiR167 was also up-regulated in the internodes of Alternanthera plants (Li et al, 2017) and Populus seedlings (Ren et al, 2012) and down-regulated in Lotus seedlings under submersion (Jin et al, 2017), probably to control some of the diverse roles of ARF transcription factors in different tissues (i.e., shoot/petiole elongation) in response to flooding.…”
Section: Rna Dynamics Under Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…These single time points have been logically chosen to provide the largest opportunity to capture relevant data but do not attempt to identify temporal relationships. Those studies that examine time series data [ 64 , 65 ] rely upon intra-time point comparisons with the advantage of assessing changes for individual molecules from time point to time point but do not address how a change in one entity at one time point might impact a different entity at a different time point. The present study includes very acute time points, 1 h, 3 h, and 6 h, as well as time points 24 and 48 h post-treatment.…”
Section: Discussionmentioning
confidence: 99%